THE EFFECT OF CREDIT RISK AND LIQUIDITY RISK AGAINST SYSTEMIC RISK IN FOUR ASEAN BANKS - Pangestuti, Rinda Siaga (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2018)
This study examines the effect of credit risk and liquidity risk on the potential of increases insystemic risk of the banking sector in four ASEAN banks. Two systemic risk measures, namelydCoVaR (Girardi and Ergun, 2013) and MES (Acharya, 2010) are used in order to evaluate theeffect of credit risk and liquidity risk on systemic risk of individual bank (dCoVaR) and systemic riskwhen the market is in distress (MES). The result from the regressions shows that credit risk andliquidity risk significantly affect systemic risk at the market distress. Meanwhile, credit risk andliquidity risk do not affect systemic risk of individual bank. That crisis affects systemic risk is foundby the two regressions which are conducted in four ASEAN banks. The result is interesting becausewhen the regression is conducted for all the countries, there is a positive and significant effect of crisis on systemic risk in four ASEAN banks, but when it is conducted for each country (as anadditional analysis), not all the countries are affected by the crisis.Keywords: systemic risk, credit risk, liquidity risk